Evaluation approach on public‐private partnership (PPP) urban redevelopments - Leung, Barbara Y.P.; Hui, Eddie C.M. (International Journal of Strategic Property Management, 2010)
Urban redevelopments in recent years tend to follow a pragmatic market‐led partnership approach with involvement of both public and private sectors. However, it has been evidenced that this approach suffers from a number of deficiencies. These include over‐reliance on private investments which make the project vulnerable to financial risks and over‐emphases on creating a place of opportunity rather than improving the social environment in the deprived areas. This paper proposes an approach encompassing Cost‐Benefit Analysis (CBA) and Option Pricing concepts (OP) into urban renewal projects which is considered more appropriate for urban redevelopment appraisal. The approach is applied for appraising the bust‐boom saga of the London Docklands redevelopment to demonstrate the importance of the inclusion of social costs and benefits in the evaluation and the strategic value of operating options. Furthermore, key factors for an urban redevelopment project are also identified from the analyses which are considered crucial for the success of the project. First Published Online: 18 Oct 2010